2016
DOI: 10.1088/0268-1242/31/11/115003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Li doping on the morphology and luminescence of Ga2O3microrods grown by a vapor-solid method

Abstract: Gallium oxide microrods have been grown by an evaporation-deposition method by using a precursor containing lithium in order to check the influence of such dopant on the morphology and physical properties of the obtained β-Ga2O3 structures. SEM studies show that the morphology is modified with respect to undoped gallium oxide, promoting the growth of micropyramids transversal to the microwire axis. Raman analysis reveals good crystal quality and an additional Raman peak centred at around 270 cm -1 , characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Luminescence from semiconducting oxides usually present broad visible emission bands often controlled by donor-acceptor pair (DAP) radiative recombinations, in which oxygen vacancies play the major role as donor levels while cation vacancies are responsible for the acceptor levels. [12][13][14] Visible emission bands have also been reported in Zn 2 GeO 4 and attributed to the above mentioned DAP recombination processes in a general way. 15,16 Moreover, its luminescence has been found to be influenced by the synthesis route of the material, signaling that not only vacancies but also interstitial defects could play an active role in the optical response.…”
mentioning
confidence: 74%
“…Luminescence from semiconducting oxides usually present broad visible emission bands often controlled by donor-acceptor pair (DAP) radiative recombinations, in which oxygen vacancies play the major role as donor levels while cation vacancies are responsible for the acceptor levels. [12][13][14] Visible emission bands have also been reported in Zn 2 GeO 4 and attributed to the above mentioned DAP recombination processes in a general way. 15,16 Moreover, its luminescence has been found to be influenced by the synthesis route of the material, signaling that not only vacancies but also interstitial defects could play an active role in the optical response.…”
mentioning
confidence: 74%
“…It has been demonstrated that doping of Ga 2 O 3 with tungsten (W) and titanium (Ti) provides enhanced ability to obtain tunable and controlled optical properties. , Additionally, Oleksak et al have demonstrated that W-doped Ga 2 O 3 thin films can form dense low- k dielectric materials, where the relative W content can significantly alter the dielectric constant . The Ga 2 O 3 nanowires doped with Li or In shown enhanced luminescence for application in display devices. , The enhanced photocatalytic activity, which may be useful in a wide variety of energy-harvesting devices, has been reported for transition metal ion-doped Ga 2 O 3 and Ga 2 O 3 hybrid materials …”
Section: Introductionmentioning
confidence: 99%
“…[35] In other systems, such as Li doped TiO2, this emission has been observed slightly shifted at 724 nm. [36] In Li doped Ga2O3, I. López et al [37] observed the presence of a narrow and intense emission around 717 nm (1.73 eV), which was associated with the intra-ionic emission of Li + ions between the 2 S-2 P0 levels again. Even when this energy could be shifted from one matrix to another, [38] in our case a possible relation of the weak emission at 1.5 eV observed in the PL spectrum in Figure 8 with the intra-ionic transitions of Li + ion could be discarded.…”
Section: Resultsmentioning
confidence: 96%